The reduction in the biomass of cyanobacterial N(2) fixer and the biological pump in the Northwestern Pacific Ocean - Kim, Dongseon (Sci Rep, 2017)
The comparison of sediment trap data with physical and biogeochemical variables in the surface water column of the Tropical Northwestern Pacific Ocean (TNWPO) indicated that the magnitude of the springtime biological pump has reduced with time due to a corresponding decrease in the biomass of cyanobacterial N(2) fixer. The decrease in the biomass of N(2) fixer likely resulted from a reduction in phosphate concentrations in response to surface water warming and consequent shoaling of the mixed layer depth during the study period (2009−2014). The same reduction in biological pump was also observed during summer. However, the cause of the summer reduction remains uncertain and is worth assessing in future studies. Our findings have major implications for predicting future trends of the biological pump in the TNWPO, where significant warming has occurred.